Modification of Three Types of Bentonite with Zirconium Oxide Chloride (ZOC) of Local Products Using Intercalation Process - Muzakky Muzakky; Supriyanto C (Universitas Gadjah Mada, 2016)
Three types of bentonite modified with ZOC local products of Center for Accelerator Science and Technology-National Nuclear Energy Agency using intercalation process have been done. The purpose of this research is to create new material as a catalyst or industrial raw materials. Existance of chloride anion on the intercalation process product was releasing with water and titration using silver nitrate. The release of alkali and alkaline earth cations and Fe3+, Al3+ and Zn3+ into the water phase (WP) and the solids phase (SP) was detected by atomic absorption Spectrometry (AAS). While X-Ray Fluorescence (XRF) was to observe of Zr intercalated to bentonite layer. Modificated products were form of a porous material and their measured as micro, meso and macro pores using Surface Area Analysis (SAA) and the image of the porous material was observed by Transmission Electron Microscopy (TEM). Intercalation process products obtained were porous materials with a porous size of 1.50-1.55 nm at bentonite-3 with a pore area of 2250 (m2/Å/g) and TEM image of the 50 nm was the most transparent among the others. As for the pores size of 1.60-1.97 nm to meso pores size of 2.0-50.0 nm were dominated by bentonite 2 with a maximum of pore 1250 (m2/Å/g). While the results of the TEM image of bentonite 2, although their porous degree were small they have the pores size distribution of 5.7% micro-pore, 52.5% meso-pore and 41.7% macro-pore.